Hubungan Pola Asuh Demokratis Orangtua dengan Motivasi Berprestasi Siswa - Jumiati, Jumiati; Mudjiran, Mudjiran (ALSYS, 2023)
This research is motivated by a phenomenon in the field which shows that there are students who do not care about achievement. Both academic and non-academic achievements. This was also found at the Man 4 Agam school. There are many factors that cause students to not have achievement motivation, including a lack of personal responsibility in carrying out a task or activity. Achievement motivation is something important that must exist within an individual. With achievement motivation, a person will be encouraged to achieve their targets and goals. This research is quantitative research with a correlational descriptive approach. The aim of this research is to find out the relationship between parents' democratic parenting style and students' achievement motivation at MAN 4 Agam. The population in this study was 275 students at MAN 4 Agam consisting of classes X, XI and XII. The number of samples in this study was 111 MAN 4 Agam students with democratic parenting patterns. The sampling technique used in this research was purposive sampling. The data collection instrument used a Likert scale model questionnaire with direct distribution of the questionnaire. Hypothesis testing was carried out using the product moment correlation analysis technique from SPSS 20. The results of this study showed 1) the majority of parents of MAN 4 Agam students who implemented democratic parenting were in the high category (49.5%). 2) Most MAN 4 Agam students' achievement motivation tends to be high (61.3%). 3) There is a very weak relationship between parents' democratic parenting style and students' achievement motivation. This means that parents' high or low levels of democratic parenting do not really influence students' achievement motivation.